The thermal process for hardening the nitrocarburized layers of a low-carbon steel. (15th March 2022) - Chen, Wanglin; Huang, Yonghao; Xiao, Hui; Meng, Xianna; Li, Zhe; Chen, Zhaoxiang; Hong, Yue; Wu, Cuilan
Abstract: Undesirable microstructures, with thin or uneven compound layers, pores, pearlitic structures, vein-like nitrides, etc., are detrimental to mechanical and tribological properties of nitrocarburized components. Here, we report a novel heat process in which a thicker nanobainitic layer, consisting of γ′ lamellas and α-Fe laths with high-density α′′-phase GP-zones, is obtained by heating the undesirable nitrocarburized layer at 700 °C (austenitizing) followed by isothermal aging at 225 °C for 14 h. The total phase-transformation sequences of this process are described as: ε + γ′ → γ-N/C → γ′ + α-Fe + GP-zones. The thicker nanobainitic layer exhibits much higher hardness, load-bearing capacity, fracture toughness and wear resistance as compared to the nitrocarburized layer, and corresponding mechanisms for strengthening and toughening are shown. Graphical abstract: Image, graphical abstract